The Application of Information Gap Activity to Improve Speaking Skill of Nursing Students - Abdul Aziz Rifaat; Nyayu Yayu Yayu Suryani (Institut Agama Islam Negeri Palopo, 2020)
Nowadays, Speaking as one of four skills taught in English become popular and very important to be learned. Since 4.0 revolution era has been launched, the students from junior high school to university level are interested to study English especially speaking skill. The study aimed to investigate the significant difference in speaking achievement before and after the students were taught using Information Gap Activity. The pre-experimental design through one group pretest-posttest design was used in this study. The 4th semester students of S1 Nursing Science program at STIK Siti Khadijah Palembang in academic year 2019/2020 was the population of this study. The sample of this study was all of the population of this study. Since the total number of the population was 22 students, they all selected as the sample in this study. The test was administered twice as pretest and posttest. The result of the test was analyzed by using t-test through SPSS (Statistical Package for Social Science).